ANALISIS STRATEGI PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT (CBT) DI DAYA TARIK WISATA PANTAI PURU, DESA MERBAUN, KECAMATAN AMARASI BARAT, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR - Radja, Maya Septiani (Jurusan Pariwisata Politeknik Negeri Kupang, 2019)
Puru Beach has the potential to attract tourists to visit. But lack of adequate facilities, poor road access, no attractive tourist attractions, minimal Human Resources (HR) managers, and no active role of local government so that it becomes problems to development of Puru Beach. The purpose of this research is to determine the community based tourism development strategy in Puru Beach. This research used a qualitative research method with the technique of taking informants using purposive sampling technique. Data collections in this research used primary data sources and secondary data sources. Data collection techniques carried out by observation, interviews, literature studies, and documentation studies. The analytical tool used to formulate community based tourism development strategies on Puru Beach is SWOT Analysis by looking at internal factors (strengths and weaknesses) and external factors (opportunities and threats) that exist in Puru Beach. Based on the results of the SWOT analysis community based tourism development strategies in Puru Beach can be formulated to make Puru Beach a Sport Tourism, increase promotional media through social media, increase human resources (HR), add supporting facilities, encouraging local governments to improve road access, collaborating with local governments, optimizing tourism awareness groups on Puru Beach, and maintaining cultural values.